ADOLESCENT REPRODUCTIVE AND SEXUAL HEALTH PROMOTION PROGRAM: REVIEW ARTICLE - Panjaitan, Arip Ambulan; Nugraheni, Sri Achadi (Krafon Publishing, 2019)
Adolescents have a high burden of sexual and reproductive health problems and it is important to reach out to youth groups through health promotion initiatives. A literature review was carried out to identify the elements of a successful health promotion program to improve adolescent reproductive health and sex. This study identified and compiled a literature review published in 2000-2018 that focused on adolescents (10-24 years), reported reproductive and sexual health outcomes (pregnancy, sexually transmitted infections, condoms / contraceptive use, risky sexual behavior, access to health care sexual or intimate partner violence), and includes major studies that are mainly carried out in high-income countries. This report focuses on the features of the reproductive and sexual health program that were successfully identified in the interpretation and discussion of the systematic reviews included. This study identified 66 systematic reviews, of which 37 were reported on programs that were anecdotally or statistically related to the increase in program effectiveness and success. The general characteristics of effective interventions are: long-term or recurrent implementation; multi-regulation and multi-component; parental involvement; according to culture, gender, age; and the inclusion of skill development. There is a marked consistency of features increasing the effectiveness of reproductive and sexual health programs for adolescents even though wide variations in interventions are reviewed. There is a need to better implement this knowledge in future programs, and our findings provide useful guidance for optimizing the design of reproductive and sexual health interventions for adolescents.